(untitled) (Al-Qamar, 2022)
In this research, a discussion has been presented on the expenditures of Zakāt in the light of the opinions of Mufassirin and Fuqaha in such a way that a review of modern issues related to expenditures has also been included in it. Since Zakāt is one of the most important pillars of Islam and is also an important source of individual and collective economic welfare of Muslims. Therefore, the need for its contemporary interpretation and explanation by making it a topic of discussion in every era will remain. In this discussion, it has been proved that the eight expenditures which are mentioned in the verse 61 of Surah Tawbah, no more can be added to these expenses in the light of the Tafaseer. Apart from this, the opinions of the ancient Fuqaha have been brought under discussion with the interpretation and analysis of Imam Razi, may God have mercy on him. Then, after describing each usage, its contemporary research has been presented and the important modern jurisprudential issues have been summarized in the discussion and it has been made comprehensive.